Analisis Terhadap Pandangan Pluralisme dan Eksklusivisme di Kalangan Gereja-Gereja di Papua pada Masa Kini - Hulu Kobak; Cristian Seldjatem (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This article discusses the current views of pluralism and exclusivism among churches in Papua, focusing on how these concepts are understood and applied in the diverse social, cultural and religious context of Papua. Pluralism recognizes religious diversity and opens space for interfaith dialogue and cooperation, while exclusivism emphasizes that salvation can only be achieved through faith in Jesus Christ. In the context of Papua, which consists of various tribes, customary traditions, and religions, churches face challenges in determining attitudes towards pluralism and exclusivism, which have an impact on interfaith relations and social dynamics in the region. The purpose of this study is to analyze how pluralism and exclusivism affect the role of churches in Papua in dealing with religious and cultural diversity. It also aims to reveal the different views among the more pluralist and exclusivist churches and how these views shape their strategies in building relationships with other communities in Papua.